Structural characterization of stem cell factors Oct4, Sox2, Nanog and Esrrb disordered domains, and a method to detect phospho-dependent binding partners - Bouguechtouli, Chafiaa; Ghouil, Rania; Alik, Ania; Dingli, Florent; Loew, Damarys; Theillet, Francois-Xavier (Comptes Rendus. Chimie)
The combined expression of a handful of pluripotency transcription factors (PluriTFs) in somatic cells can generate induced pluripotent stem cells (iPSCs). Here, we report the structural characterization of disordered regions contained in four important PluriTFs, namely Oct4, Sox2, Nanog and Esrrb. Moreover, many post-translational modifications (PTMs) have been detected on PluriTFs, whose roles are not yet characterized. To help in their study, we also present a method (i) to produce well-characterized phosphorylation states of PluriTFs, using NMR analysis, and (ii) to use them for pull-downs in stem cell extracts analyzed by quantitative proteomics to detect potential Sox2 binders.